1995
DOI: 10.1037/1064-1297.3.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine reuptake inhibitors on food- and cocaine-maintained responding: I. Dependence on unit dose of cocaine.

Abstract: The effects of the high-affinity dopamine reuptake inhibitor, GBR 12909, were studied on responding maintained under multiple fixed ratio schedules of food and cocaine delivery in rhesus monkeys (Macaca mulatta). GBR 12909 decreased rates of responding maintained by both events in a dose-related manner, however large decreases in cocaine-maintained responding could be obtained with doses of GBR 12909 that had little effect on food-maintained responding. This behaviorally selective effect of GBR 12909 on cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 34 publications
11
78
1
Order By: Relevance
“…Other compounds have been identified that had a ratio value Ͼ1, but without cocaineantagonist effects (Wang et al, 2000;Xu et al, 2002). Along similar lines, the DA uptake inhibitor GBR 12909 antagonized the increase in extracellular DA concentration after administration of cocaine (Rothman et al, 1991) and produced selective decreases in selfadministration of cocaine (Glowa et al, 1995). Although there are many differences among the results of all of these studies, a general conclusion is that not all DA uptake inhibitors produce effects identical to those of cocaine and that, under certain conditions, antagonist effects may be obtained.…”
Section: Discussionmentioning
confidence: 83%
“…Other compounds have been identified that had a ratio value Ͼ1, but without cocaineantagonist effects (Wang et al, 2000;Xu et al, 2002). Along similar lines, the DA uptake inhibitor GBR 12909 antagonized the increase in extracellular DA concentration after administration of cocaine (Rothman et al, 1991) and produced selective decreases in selfadministration of cocaine (Glowa et al, 1995). Although there are many differences among the results of all of these studies, a general conclusion is that not all DA uptake inhibitors produce effects identical to those of cocaine and that, under certain conditions, antagonist effects may be obtained.…”
Section: Discussionmentioning
confidence: 83%
“…This is the first study to evaluate the effects of a candidate pharmacotherapy on cocaine vs food choice under different behavioral conditions; however, the results of this study agree with previous studies using other schedules of reinforcement that self-administration of lower unit doses of cocaine is more vulnerable than responding maintained by higher cocaine doses to various manipulations including treatment with candidate medications. For example, both the selective dopamine uptake inhibitor GBR12909 (Glowa et al, 1995) and the monoamine releaser d-amphetamine were more potent to reduce self-administration maintained by lower than higher unit doses of cocaine under multiple schedules of sequential cocaine and food availability in rhesus monkeys.…”
Section: Effects Of Phenmetrazine On Cocaine Choicementioning
confidence: 99%
“…Compared to the same doses of cocaine, GBR-12909-induced increases in striatal DA and locomotion are relatively slow-onset and long-lasting (Baumann et al, 1991(Baumann et al, , 1994Kelley and Lang, 1989). Pretreatment with GBR-12909 significantly inhibits cocaine self-administration in rats and nonhuman primates at doses that have little or no effect on food self-administration (Glowa et al, 1995). Repeated treatment with low doses of GBR-12909 sustains the selective suppression of cocaine self-administration versus food selfadministration (Glowa et al, 1995).…”
Section: Gbr-12909mentioning
confidence: 99%
“…Pretreatment with GBR-12909 significantly inhibits cocaine self-administration in rats and nonhuman primates at doses that have little or no effect on food self-administration (Glowa et al, 1995). Repeated treatment with low doses of GBR-12909 sustains the selective suppression of cocaine self-administration versus food selfadministration (Glowa et al, 1995). Further, a single injection of a slow-release formulation of GBR-12909 produced a prolonged (up to one month) suppression of cocaine selfadministration in nonhuman primates (Glowa et al, 1996).…”
Section: Gbr-12909mentioning
confidence: 99%